Characterisation of 11beta-hydroxysteroid dehydrogenase 1 in human orbital adipose tissue: a comparison with subcutaneous and omental fat. - Bujalska, I; Durrani, O; Abbott, J; Onyimba, C; Khosla, P; Moosavi, A; Reuser, T; Stewart, P; Tomlinson, J; Walker, E; Rauz, S (2007)
Glucocorticoids (GCs) have a profound effect on adipose biology increasing tissue mass causing central obesity. The pre-receptor regulation of GCs by 11beta-hydroxysteroid dehydrogenase type 1 (11beta-HSD1) that activates cortisol from cortisone has been postulated as a fundamental mechanism underlying the metabolic syndrome mediating adipocyte hyperplasia and hypertrophy in the omental (OM) depot. Orbital adipose tissue (OF) is the site of intense inflammation and tissue remodelling in several orbital inflammatory disease states. In this study, we describe features of the GC metabolic pathways in normal human OF depot and compare it with subcutaneous (SC) and OM depots. Using an automated histological characterisation technique, OF adipocytes were found to be significantly smaller (parameters: area, maximum diameter and perimeter) than OM and SC adipocytes (P<0 x 001). Although immunohistochemical analyses demonstrated resident CD68+ cells in all three whole tissue adipose depots, OF CD68 mRNA and protein expression exceeded that of OM and SC (mRNA, P<0 x 05; protein, P<0 x 001). In addition, there was higher expression of glucocorticoid receptor (GR)alpha mRNA in the OF whole tissue depot (P<0 x 05). Conversely, 11beta-HSD1 mRNA together with the markers of late adipocyte differentiation (FABP4 and G3PDH) were significantly lower in OF. Primary cultures of OF preadipocytes demonstrated predominant 11beta-HSD1 oxo-reductase activity with minimal dehydrogenase activity. Orbital adipocytes are smaller, less differentiated, and express low levels of 11beta-HSD1 but abundant GRalpha compared with SC and OM. OF harbours a large CD68+ population. These characteristics define an orbital microenvironment that has the potential to respond to sight-threatening orbital inflammatory disease.